2022
DOI: 10.1111/dme.14830
|View full text |Cite
|
Sign up to set email alerts
|

Parental smoking, type 1 diabetes, and islet autoantibody positivity in the offspring: A systematic review and meta‐analysis

Abstract: Aims Our aim was to synthesize current evidence on the association between parental smoking and incidence of type 1 diabetes and islet autoantibody positivity (IA) in the offspring by conducting a systematic review and meta‐analysis. Methods We searched Medline, Embase, and Cochrane Library until January 21, 2021, for human studies with parental tobacco use as exposure, type 1 diabetes or IA as outcome, and hazard, risk, or odds ratios as effect estimates. Summary relative risks (RR) and 95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…This nationwide prospective study shows that children exposed to maternal smoking during pregnancy have a 22% lower risk of developing type 1 diabetes during childhood compared to their unexposed siblings. This confirms the results of previous observational studies [3,45] and suggests that maternal smoking during pregnancy has the potential to prevent offspring type 1 diabetes.…”
Section: Main Findingssupporting
confidence: 91%
See 3 more Smart Citations
“…This nationwide prospective study shows that children exposed to maternal smoking during pregnancy have a 22% lower risk of developing type 1 diabetes during childhood compared to their unexposed siblings. This confirms the results of previous observational studies [3,45] and suggests that maternal smoking during pregnancy has the potential to prevent offspring type 1 diabetes.…”
Section: Main Findingssupporting
confidence: 91%
“…We addressed this association using cohort, sibling, and cousin designs, the latter two of which allowed us to control for potential unmeasured confounders shared within families. The observed association between maternal smoking during pregnancy and offspring type 1 diabetes was consistent across the three designs, and the effect size was in line with the RR of 0.78, observed in a recent meta-analysis based on 22 studies [4]. It was also consistent with the pooled RR of 0.72 reported in another meta-analysis based on five population-based prospective studies [3].…”
Section: Main Findings In Relation To Previous Studiessupporting
confidence: 88%
See 2 more Smart Citations
“…Smoking is associated with an increased risk of type 2 diabetes ( 64 ). In contrast, a reduced risk of type 1 diabetes is consistently observed in the offspring of mothers who smoked during pregnancy ( 65 ). Earlier findings based on the Norwegian HUNT-study and data collected between 1984 and 2008 suggested that smokers may have a reduced risk of LADA ( 66 ).…”
Section: Lifestyle or Environmental Factorsmentioning
confidence: 99%